Clinical characteristics and outcomes of neonatal SARS-CoV-2 infection after the release of the epidemic situation of COVID-19 - Siyi Xia; Fei Bei; Cheng Cai; Liqing Xu; Xiaohui Gong; Jingjing Wang; Yongjun Zhang; Huafei Huang; Hongping Xia (BMC, 2024)
Abstract Background With the release of the coronavirus disease 2019 (COVID-19) pandemic in late 2022 in China, the number of people infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) roared, including neonatal cases. However, there were few studies on neonatal COVID-19, especially multi-center case reports. This study aimed to explore clinical characteristics and short-term outcomes of neonatal COVID-19 in China. Methods We reviewed 187 cases of neonatal COVID-19 between December 11, 2022, and January 12, 2023. The diagnosis was assessed by symptoms, laboratory tests, X-ray manifestations, and diagnosis code. Clinical characteristics and outcomes were evaluated. Results In 187 neonatal cases with COVID-19, 84 (44.9%) had severe SARS-CoV-2 infection. Most patients had confirmed exposure to SARS-CoV-2. Fever and respiratory symptoms were common (75.4% and 71.7%, respectively). Severe patients were more likely to have high alanine transaminase (ALT) (> 40U/L) (11.9% vs. 3.9%) and high N-terminal pro-brain natriuretic peptide (NT-proBNP) (> 2000pg/mL) (38.0% vs. 19.6%), compared with nonsevere ones (P < 0.05). None of the patients received COVID-19-specific medical interventions. A few severe patients received corticosteroids (1.1%), and immunoglobulin (0.5%), respectively. All patients were discharged home after the medical care with a median length of stay (LOS) of four days and none of them met the criteria of multisystem inflammatory syndrome in neonates (MIS-N). Conclusions After the release of the epidemic situation of COVID-19 in late 2022 in China, more neonatal cases with severe COVID-19 had high ALT and NT-proBNP level. Few specific medical interventions were given, and the outcome was satisfying.